Perancangan Meja Dan Kursi Ergonomis Sebagai Fasilitas Gaming - Felicia Aprillina; Grace Mulyono; Franky Tanaya (Intra, 2019)
Nowadays, the e-sports world is becoming more popular and favoured among people from all kinds. Gamers  definitely need supporting equipment in order to perform well in the game. However, the gaming equipments are quite expensive and not affordable to most people. The solution offered to this problem is to design an up-to-date, ergonomic, and low-budget gaming equipment (desk and chair), to be affordable for all gamers. Therefore, the author used leftover wood pieces as a new innovation in designing computer desks.